A Cartography of Angry Indian Goddesses towards Nomadic Affect - Indrani Mukherjee (Universitat Autònoma de Barcelona, 2019)
This paper attempts to draw a cartography of becoming Angry Indian Goddesses as transnational nomadism towards an embodied and material rethinking of women’s friendships from outside the constraints of systemic binaries. The friends are all professional women who are globally wired, whose thinking minds and non-docile bodies detach themselves from any normative modes of belonging in their respective personal and professional realms. They map a post-humanist spatiality of rhizomic linkages with other animate and non-animate entities, throwing up a new ethics of nomadic affect and responsibility.  The film begins with a panoramic gaze of the Goan landscape, overlapped with flash images of Hindu goddesses and their animal escorts framed within a power packed song “Kattey”, which intersects Bhanwari Devi’s powerful folk composition of Meera Bai’s 15th century mystic tradition with Haard Kaur’s rap. The crossing of the song and the violent events of rejection that the women face, unbridle a becoming angry goddesses through a pastiche of the anxious goddesses and women sited on an axis of re/de-valorised difference. Goa becomes a potential third space entangled with all of the above, as it dwells on the contemplative scope of this cartography as redemptive and suggests a re-humanization of schizophrenic splintered objects through love and affect.